(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Protecting private medical pictures while also facilitating their widespread distribution and use has made secure watermarking a vital component of modern healthcare informatics. Algorithms for Dual watermarks on medical images are presented in this work. Two watermarks, one for the company logo and one for the EHR. Space is conserved, attachments are avoided, network traffic is reduced, etc. The results demonstrate that the suggested system’s accuracy will improve and that it provides a high PSNR value. Telemedicine, medical research, legal and forensic applications, increased security, and improved partnerships are just few of the areas that may benefit from the use of secure medical image watermarking.